Simulation of exchange routes on the Qinghai-Tibetan Plateau shows succession from the neolithic to the bronze age and strong control of the physical environment and production mode - Lancuo, Zhuoma; Hou, Guangliang; Xu, Changjun; Jiang, Yuan; Wang, Wen; Gao, Jingyi; Wende, Zhuoma (Frontiers in Earth Science, 2023)
The Qinghai-Tibetan Plateau (QTP) is essential for converging eastern, western, and northern prehistoric cultural spheres of Asia and Europe and for human adaptation to extreme environments. Reconstruction of the location and development of prehistoric exchange routes on the Qinghai-Tibetan Plateau underpins understanding human response to harsh environments and interaction and exchange between the three cultural spheres. This study simulates exchange routes for the Neolithic and Bronze Ages, using elevation, slope, vegetation, and rivers as cost data and site points as node data. A weighted network consisting of nodes and lines is constructed within the Qinghai-Tibetan Plateau using a weighted cumulative cyclic connectivity model among nodes-the simulation abstracts exchange routes as a path search problem on this weighted network. The final simulated route is the road with the lowest incremental cost. The results give a total length of Neolithic routes of about 16,900 km, with 15 main roads, and a total length of Bronze Age routes of approximately 16,300 km, with 18 main roads. Pathway development from the Neolithic to the Bronze Age shows an apparent successional relationship, with a spatial evolution from the marginal corridor to the marginal hinterland. The simulated routes overlap highly with archaeological evidence for transmission routes of corn and millet agriculture and wheat agriculture-domesticated animals-bronze metallurgy technology, indicating the reliability of the simulation results. Further analysis showed that the unique physical geography of the QTP constrained the formation and evolution of routes. River valleys were commonly chosen as routes to acclimatize people to the high, cold, and low oxygen levels of the Qinghai-Tibetan Plateau. Scattered small agricultural bases, established in areas of the QTP suitable for agricultural planting, are the basis for intersecting exchange routes. Road formation also reflects the clear differentiation in the agro-pastoral industry between high and low altitudes related to climate, ecological environment, and elevation. Interaction between agricultural and nomadic populations is the crucial motivation for forming and developing the exchange routes.